Antibacterial performance of bovine lactoferrin-fish gelatine electrospun membranes - Padrão, Jorge (2015)
The increase of antibiotic resistant microorganisms urged the development and synthesis of novel antimicrobial biomaterials to be employed in a broad range of applications, ranging from food packaging to medical devices. This work describes the production and characterization of a protein-based electrospun fibrous membranes bearing antimicrobial properties. Its composition is exclusively comprised of proteins, with fish gelatine as structural matrix and bovine lactoferrin (bLF) as the active antimicrobial agent. The bLF bactericidal effect was determined against clinical isolates of Escherichia coli and Staphylococcus aureus through microdilution assays. Two distinctive methods were used to incorporate bLF into the fish gelatine nanofibres: (i) as a filler in the electrospinning formulation with concentrations of 2, 5 and 10 (wt%), and cross-linked with glutaraldehyde vapour, in order to achieve stability in aqueous solution; and (ii) through adsorption in a solution with 40 mg mL1 bLF. Fourier transform infrared spectroscopy analysis showed that the structure of both proteins remained intact through the electrospinning blending and cross-linking procedure. Remarkable antibacterial properties were obtained with membranes containing 5% and 10% bLF with a bacterial reduction of approximately 90% and 100%, respectively.